2013
DOI: 10.1590/s0103-20032013000400007
|View full text |Cite
|
Sign up to set email alerts
|

Pesquisa Qualitativa: rigor metodológico no tratamento da teoria dos custos de transação em artigos apresentados nos congressos da Sober (2007-2011)

Abstract: Resumo: O objetivo deste artigo foi analisar como são construídas as pesquisas de natureza qualitativa em artigos sobre a Teoria dos Custos de Transação (TCT), considerando as publicações dos anais da Sociedade Brasileira de Economia, Administração e Sociologia Rural (Sober), de 2007 a 2011. Foram focados aspectos metodológicos relacionados aos tipos de pesquisa, recorte temporal, métodos de coleta, tipos de dados e métodos de análise utilizados. Para tanto, realizou se uma pesquisa qualitativa, do tipo descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
46

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 3 publications
0
7
0
46
Order By: Relevance
“…Requested by the e-SIC system, received at the end of the year 2015, are considered here as primary data [20] conception that considers primary data those that present a direct physical relationship With the facts analyzed, that is, they were collected specifically for a given investigation [21]. The temporal cut of the transverse cut type with a longitudinal perspective was established [20] for the period from 2000 to 2015.…”
Section: Methodsologymentioning
confidence: 99%
“…Requested by the e-SIC system, received at the end of the year 2015, are considered here as primary data [20] conception that considers primary data those that present a direct physical relationship With the facts analyzed, that is, they were collected specifically for a given investigation [21]. The temporal cut of the transverse cut type with a longitudinal perspective was established [20] for the period from 2000 to 2015.…”
Section: Methodsologymentioning
confidence: 99%
“…Ambiguity, characterized as lack of ability to perform a previously planned childcare activity, prevents parents from plotting both short-and long-term plans. 22 In addition, cognitive ability, which directly influences the understanding of information was shown to be related, among other factors, to the level of parents' schooling, showing an inverse relationship with the level of uncertainty. 17 Unpredictability, also called by Mishel as probabilistic thinking, was a factor that increased the uncertainty of the parents, bringing, also, concern emerging from the unknown and lack of control.…”
Section: • Contributors To Increased Uncertaintymentioning
confidence: 97%
“…person's stimulus framework and may reduce or increase uncertainties. [20][21][22] One of the studies showed a significant negative association between the low socioeconomic level, the fact of not having a spouse and the level of uncertainty (8). 17 In all studies, the sample consisted of parents of preterm newborns, demonstrating the researchers' great interest in understanding the emotional phenomena that are related not only to the newborn's hospitalization but, above all, to prematurity.…”
Section: Figure 3 Synthesis Of the Theme Addressed In The Workmentioning
confidence: 99%
“…Os dados documentais foram obtidos com os gestores do programa no nível municipal e por meio do sitio eletrônico do Ministério da Saúde. Foram realizadas entrevistas semiestruturadas 21,22 com seis gestores da área da saúde (um federal, um estadual e quatro municipais), três profissionais que atuam na atenção básica, sete gestores municipais da área da educação e quinze profissionais que atuam nas escolas diretamente envolvidos com o PSE e com o processo de implementação do Nutri-SUS no município. A seleção dos entrevistados se pautou na proximidade com a gestão e operacionalização do NutriSUS nos diferentes setores e subsetores municipais e níveis de governo envolvidos, sendo definida ao longo do processo de investigação.…”
Section: Desenho Do Estudo E Referencial Metodológicounclassified